Ideologijos ir istoriografijos įtaka Lietuvos Didžiosios Kunigaikštystės istorijos aktualinimui. Lietuvos dokumentinio diskurso (1988-2007 m.) analizė - Šermukšnytė, Rūta (Lietuvos istorijos studijos, 2009)
The article explains ideological and historiographic influences on the popularization of the history of the Lithuanian Grand Duchy within the discourse of Lithuanian documentary film and television from 1988 to 2007. The problem of the study arises from the unclear relationship between the ideological goals of national mobilization and the orientation documentarians set for themselves during the period of Rebirth, and the task of publishing scientific research, considered one of the essential functions of documentaries. The article uses specific film and TV examples to support two assertions: (1) The ideological intentions of film and TV authors give priority to explanations of the past influenced by the ideology of nationalism; (2) The preference among film and TV authors for critical Lithuanian historiography in terms of nationalist interpretations is associated with the goals they have set for themselves of revising concepts of the past that have taken hold in society.